Hierarchical Targeting Strategy for Enhanced Tumor Tissue Accumulation/Retention and Cellular Internalization - Wang, Sheng (Adv Mater, 2016)
Targeted delivery of therapeutic agent is an important way to improve therapeutic index and reduce side effects. To design nanoparticles for targeted delivery, both enhanced tumor tissue accumulation/retention and enhanced cellular internalization should be considered simultaneously. Unfortunately, so far, there have been very few nanoparticles with immutable structures can achieve this goal efficiently. Hierarchical targeting, a novel targeting strategy based on stimuli responsiveness, shows good potential to enhance both tumor tissue accumulation/retention and cellular internalization. In this review, we will introduce recent design and development of hierarchical targeting nanoplatforms, which are based on changeable particle sizes, switchable surface charges and activatable surface ligands. In general, the targeting moieties in these nanoplatforms are not activated during blood circulation for efficient tumor tissue accumulation and then re-activated by certain internal or external stimuli in tumor microenvironment for enhanced cellular internalization.